Exercise Induces Autonomic and Neuro-endocrine Response among Psychologically Stressed Medical Students - Ghazala Jawwad, Humaira Fayyaz Khan, Mehwish Iftikhar, Azhar Hussain, Sidra Arshad, Lubna Siddique, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Psychological stress activates Hypothalamic- Pituitary- Adrenal axis (HPA) and Sympathoadrenal (SMA) axis”. Exercise has stress buffering action and it improves HRV and normalizes the cortisol response to stress. Aim: To evaluate the effect of moderate exercise in stabilizing autonomic and neuro-endocrine response to Psychological stress”. Study design: Randomized experimental study. Methodology: 100 MBBS students were engaged through DASS (Depression anxiety stress scale) proforma. They were divided into two groups; stress and control. HRV and serum cortisol levels were obtained. Stressed group did regular moderate exercise for 06 weeks. Independent t test was employed to see the difference in two parameters among the two groups. A p value of ≤ 0.05 was taken as significant. Results: After the intervention stressed group exhibited prominent decrease in LF/HF, LFnu, LFms2” and serum cortisol (0.009,0.033,.027 and 0.007 respectively. HFnu was significantly improved post exercise (.004). Significant reduction in serum cortisol was observed in stressed group after exercise (.007). Conclusion: Exercise can be employed to buffer the effect of psychological stress as it normalizes HPA axis” and autonomic response.